The Effect of Internal Control, Individual Morality and Ethical Value on Accounting Fraud Tendency - Fernanda Fernandhytia; Muslichah Muslichah (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2020)
In general, this study aims to determine the effect of Internal Control, Individual Morality, and ethical Value on Accounting Fraud Tendency in Start-Up Businesses. This study was conducted onÂ Start-Up Businesses. One hundred eighty-eight respondents participated in this study. The result of this study showed that internal control has a significant negative effect on accounting fraud tendency. In other words, an increase in Internal Control will decrease the tendency of accounting fraud in a company. Individual morality also has a significant negative effect on accounting fraud tendency. An increase in individual morality, which could be done by implementing the right morals in daily activity will prevent the action of fraudulent behavior. Furthermore, ethical value also has a significant negative effect on accounting fraud tendency. A proper profession ethic codes will increase moral value in an individual's professionalism, which will minimize the action of fraudulent behavior. This research is done in the hope to contribute to the theory and practice. This study contributes to the subject related to internal control, individual morality, ethical value, and accounting fraud tendency. Furthermore, for Start-Up Businesses, research can be used to prevent accounting fraud